SPE Annual Technical Conference and Exhibition 2005
DOI: 10.2118/96116-ms
|View full text |Cite
|
Sign up to set email alerts
|

Injection Strategies for Foam Generation in Homogeneous and Layered Porous Media

Abstract: Foam generation plays a crucial role in the use of foam for improved oil recovery, acid diversion and environmental remediation.This sandpack study extends previous work to layered media, the effect of surfactant concentration, and injection strategy, including alternating-slug (SAG) injection and pulsed injection rate and pressure.As in earlier studies, three foam states were observed: high-mobility coarse foam at low pressure gradient, low-mobility strong foam at high pressure gradient, and, in between, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 29 publications
1
21
2
Order By: Relevance
“…It was also found that a secondary desaturation front propagated in the direction opposite the foam propagation during coinjection processes (Simjoo et al 2013), which was similar to the observations in other studies (Apaydin and Kovscek 2001;Nguyen et al 2003). Some coinjection experiments require several-pore-volume injections of gas and surfactant solution to achieve a steady pressure drop across the core even after excluding the possibility of satisfying surfactant adsorption and gas compressibility (Li et al 2010;Ma et al 2013;Simjoo et al 2013), which is also not predicted by local-equilibrium foam models. Rossen and Boeije (2013) pointed out that laboratory SAG coreflooding could be unreliable to be used for parameter fitting of local-equilibrium models because of failure to reach local steady state, increased effect of dispersion, and the capillary end effect.…”
Section: Challengessupporting
confidence: 83%
See 2 more Smart Citations
“…It was also found that a secondary desaturation front propagated in the direction opposite the foam propagation during coinjection processes (Simjoo et al 2013), which was similar to the observations in other studies (Apaydin and Kovscek 2001;Nguyen et al 2003). Some coinjection experiments require several-pore-volume injections of gas and surfactant solution to achieve a steady pressure drop across the core even after excluding the possibility of satisfying surfactant adsorption and gas compressibility (Li et al 2010;Ma et al 2013;Simjoo et al 2013), which is also not predicted by local-equilibrium foam models. Rossen and Boeije (2013) pointed out that laboratory SAG coreflooding could be unreliable to be used for parameter fitting of local-equilibrium models because of failure to reach local steady state, increased effect of dispersion, and the capillary end effect.…”
Section: Challengessupporting
confidence: 83%
“…As a mobility-control agent, foam has the potential for applications in industrial processes that involve fluid injection into porous formation, such as enhanced oil recovery (EOR) (Patzek and Koinis 1990;Patzek 1996;Farajzadeh et al 2009Farajzadeh et al , 2012Li et al 2010;Ren et al 2013;Chen et al 2014), matrix-acidization treatments (Gdanski 1993;Rossen and Wang 1999;), gas-leakage prevention (Bernard and Holm 1970;Smith and Jikich 1993), and contaminated-aquifer remediation (Hirasaki et al 1997;Mulligan 2009). The success of these applications relies heavily on the understanding of the physics of foam flow through porous media.…”
Section: Introduction To Foam In Porous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…So these two mechanisms are considered to be able to generate strong foam. Pressure gradient [11][12][13][14] is important in strong foam generation process. Higher p ∇ can mobilize more stationary lamellae, set off the lamellae division process and generate more new lamellae which will block more of the gas flow paths.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, we also notice that relative to simultaneous injection (Fig. 6), the alternating injection does promote the foam generation and injectivity (Li and Rossen 2005) for both types of foams indicated by the quick strong foam propagation and lower pressure drops.…”
Section: Co-injectionmentioning
confidence: 57%